Deliberate practice and sport excellence: A diary study with Portuguese elite athletes - Matos, D. S.; Ferreira, M. J.; Cruz, J. F.; Almeida, L. S. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: The engagement in intensive and extended deliberate practice is a major assumption of the expert-performance approach in studying elite athletes. The purpose of this study was to examine the quantity and quality of practice activities in a sample of Portuguese elite athletes. The main aims were to explore how a "typical work week" of these athletes is organized, how their daily activities are perceived in terms of the qualities demanded by the "10-year rule" of necessary preparation in order to attain expertise, testing for the association between retrospectively estimated amounts of practice and "actual" practice and assessing their perceptions and characteristics of deliberate practice. Methods: 9 purposefully selected Portuguese top athletes, ranging from 18 to 35 years old (M=24,7 ± 5,4), of both genders, competing at the highest international level, who excelled in several sports (individual vs. team) completed biographic data and maintained diaries over a 7-day period. Results: The analysis of the time spent by athletes in different types of daily activities (in or out of sport context), indicated that, in average, athletes spend more time in sport-specific practice activities. Such activities are highly evaluated in terms of enjoyment, required physical effort, mental effort, relevance to performance, and general satisfaction. Additionally, data seem to support, for the most of participants, the so-called "10-year rule" of necessary preparation and also the consistency between athletes retrospectively estimated amounts of practice (biographic data) and "actual" practice (diary). These results were independent of gender, type of sport (individual vs team) or even international experience of the athletes. Discussion: The findings of this investigation provides some support for previous assumptions of deliberate practice and expert performance research (Ericsson, et al., 1993; Ericsson & Lehmann, 1996; Hodges et al., 2004), confirming the importance of the intensity and characteristics of sport-specific practice activities as a crucial factor in the qualitative difference between levels of expertise (e.g., Baker et al., 2005; Ward et al., 2007). Limitations and implications arising from this study are discussed.